Psychology 2019
DOI: 10.1093/obo/9780199828340-0229
|View full text |Cite
|
Sign up to set email alerts
|

Competency to Stand Trial

Abstract: A core principle of modern-day law is that all defendants maintain the right to a fair trial. A defendant must be able to factually and rationally understand and participate in a court process, the ability to do so deems the defendant competent. Competency is relevant through all stages of the criminal justice process from arrest through sentencing. This article describes research and scholarship related to competency to stand trial. Competency to stand trial is a doctrine of jurisprudence that requires crimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…It follows that cognitive remediation could also improve neurocognitive functioning among defendants opined incompetent to proceed. This assertion is supported by forensic mental health and neuropsychology theory (Schwalbe & Medalia, 2007; Zapf, 2013), as well as a small pilot study that revealed cognitive remediation can improve Dusky reasoning abilities, particularly among individuals diagnosed with schizophrenia (Wilson, 2015).…”
Section: Research Priorities For Forensic E-mental Healthmentioning
confidence: 91%
“…It follows that cognitive remediation could also improve neurocognitive functioning among defendants opined incompetent to proceed. This assertion is supported by forensic mental health and neuropsychology theory (Schwalbe & Medalia, 2007; Zapf, 2013), as well as a small pilot study that revealed cognitive remediation can improve Dusky reasoning abilities, particularly among individuals diagnosed with schizophrenia (Wilson, 2015).…”
Section: Research Priorities For Forensic E-mental Healthmentioning
confidence: 91%
“…This article is intended solely for the personal use of the individual user and is not to be disseminated broadly. UNRESTORABILITY AND THE DEMONSTRATION MODEL 3 restoration units far longer than those who are restored (Zapf & Roesch, 2006). Consequently, defendants who are potentially unrestorable continue to occupy a bed that could otherwise be used to treat a defendant who is adjudicated IST and waitlisted for hospitalbased restoration Gowensmith, 2019).…”
Section: Heilbrun Et Almentioning
confidence: 99%
“…of those found incompetent and subsequently referred for restoration, the majority are restored or trained back to competency (murrie & Zelle, 2015). a variety of restoration approaches and programs have been employed, ideally targeted to the defendant's deficits, including psychotropic medication, educational treatment programs focused on legal issues and communication with the attorney, and cognitive remediation (murrie & Zelle, 2015;Zapf, 2013). most restoration programs are successful.…”
Section: Restorationmentioning
confidence: 99%
“…Unfortunately, other aspects of this study, such as age or type of offense, were not specified. as a benchmark for time to restoration, Zapf (2013) observed that the average length of stay for competency restoration at a hospital in Washington state for felony defendants was 81 days and, of those restored, 78% were done within 90 days. for those restored, days to restoration for nonfelony defendants was 29 days.…”
Section: Restorationmentioning
confidence: 99%